2018
DOI: 10.1111/apa.14214
|View full text |Cite
|
Sign up to set email alerts
|

Five‐country manikin study found that neonatologists preferred using the LISAcath rather than the Angiocath for less invasive surfactant administration

Abstract: AimLess invasive surfactant administration (LISA) has been shown to decrease the risk of death and bronchopulmonary dysplasia in preterm neonates. The LISAcath is the first catheter to be specifically developed for LISA, and we compared the clinical impressions of neonatologists using the LISAcath and the commonly used Angiocath in a simulated setting.MethodsThis was a multinational, multicentre study, conducted in October 2016, which involved 39 neonatologists who were recruited by employees of the sponsor fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…We have earlier reported that this improvised MIST equivalent of the semirigid catheter technique (the prototype is the LISA catheter) is technically simpler to adapt in clinical practice [15]. This observation is in conformity with earlier reports from Europe [23][24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have earlier reported that this improvised MIST equivalent of the semirigid catheter technique (the prototype is the LISA catheter) is technically simpler to adapt in clinical practice [15]. This observation is in conformity with earlier reports from Europe [23][24].…”
Section: Discussionsupporting
confidence: 88%
“…As LISA catheter may not be readily available in all units, we later performed an improvised MIST procedure using the smallest size ETT 2.0, whose inner diameter is equivalent to 8 Fr infant feeding tube and instilled surfactant directly from a syringe attached to the hub of the ETT. Infant feeding tubes are usually made of polyurethane material that is much more flexible and hence difficult to guide into the trachea in contradistinction to the poly vinyl chloride material that is in ETT [23][24]. We have earlier reported that this improvised MIST equivalent of the semirigid catheter technique (the prototype is the LISA catheter) is technically simpler to adapt in clinical practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Routine oral intubation is more common in other parts of the world, so that the use of a stiff vascular catheter was described by Peter Dargaville et al 11 as the so-called Hobart method (minimally invasive surfactant therapy (MIST)) in 2011. Straight (LISAcath)12 or stiff catheters with an angulated tip (Surfcath) have been designed especially for the purpose of LISA via the oral route. Special introducers13 (Neocath) and devices to guide the catheter when video laryngoscopy is being used have recently been developed.…”
Section: How To Perform Lisamentioning
confidence: 99%
“…The options included LISAcath or vascular catheters, which had been used in almost 90% of infants. LISAcath was previously shown to be the most commonly used catheter in a recent survey from the UK [17,18]. Semirigid vascular catheters are also preferred by Spanish doctors [10].…”
Section: Plos Onementioning
confidence: 99%